Znanstvenoraziskovalna dejavnost Univerze v Mariboru in pogled v prihodnje / The University of Maribor’s scientific research activities and a look into the future - Karin Stana Klainschek (Acta Medico-Biotechnica, 2021)
Due to changing social and economic conditions, the University of Maribor (UM) is facing new challenges that affect how the University’s scientific research work is organised. In the future, greater integration between individual research fields and areas will be necessary in order to achieve scientific excellence, higher quality of life, greater economic growth in the region and, thereby, sustainable development. The University environment enables academic freedom, promotes creative thinking and helps to devise and realise original scientific ideas; ideas that are not always focused on the direct creation of new value–added products and technologies. Because of the increasing demand for greater economic growth, the development–industrial environment, on the other hand, offers a developmentally and industrially creative environment which is goal–oriented towards the development of a particular product. We all walk together on the path to the creation and development of our environment and a higher quality of life, in line with the European Community’s main scientific research and developmental directions, each with our own strengths and weaknesses. The role of the University in this process is to unite and coordinate with the intention of achieving synergetic and sustainable effects. The vision, mission and strategy of the scientific research work at the UM is defined by uniting teaching and research, integrating various fields and activities, and improving the transfer and sharing of knowledge.